Liposomes as colloidal nanovehicles: on the road to success in intravenous drug delivery - Naeem, Sumaira; Viswanathan, Geetha; Misran, Misni (De Gruyter, 2018)
The advancement of research in colloidal systems has led to the increased application of this technology in more effective and targeted drug delivery. Nanotechnology enables control over functionality parameters and allows innovations in biodegradable, biocompatible, and stimuli-responsive delivery systems. The first closed bilayer phospholipid system, the liposome system, has been making steady progress over five decades of extensive research and has been efficient in achieving many desirable parameters such as remote drug loading, size-controlling measures, longer circulation half-lives, and triggered release. Liposome-mediated drug delivery has been successful in overcoming obstacles to cellular and tissue uptake of drugs with improved biodistribution in vitro and in vivo. These colloidal nanovehicles have moved on from a mere concept to clinical applications in various drug delivery systems for antifungal, antibiotic, and anticancer drugs.